Pengaruh Dukungan Sosial Keluarga Dan Berpikir Positif Terhadap Resiliensi Pada Penyintas Covid-19 di Perum Griya Wiharta Asri - Afghani, Muhammad Firgy Al; Rejeki, Asri (Jurnal Ilmiah Wahana Pendidikan, 2025)
The spread of COVID-19 was first discovered in the city of Wuhan in China. COVID-19 has caused a lot of impact on human life. For exposed individuals are required to carry out isolation and receive intensive treatment without visits from anyone. Therefore, family social support and positive thinking are needed. When individuals get family social support and are able to think positively, it is hoped that they can increase their resilience abilities. This study aims to determine the effect of family social support and positive thinking on resilience in survivors of Covid-19 at Perum Griya Wiharta Asri. This research uses quantitative methods. The results of the multiple linear regression test show the sig. 0.000 <0.5 means that there is a simultaneous effect of family social support and positive thinking on resilience in survivors of Covid-19 at Perum Griya Wiharta Asri. Family social support and positive thinking variables contributed 58.6% to the resilience variable. Future researchers are expected to be able to examine using other variables that might affect resilience and also expand the criteria and broader subject.